ASSESSING THE IMPACT OF ECONOMIC POLICIES ON UNEMPLOYMENT: A BIBLIOMETRIC PERSPECTIVE (Social Security Management Journal, 2025)
This study examines the evolution and current state of research on economic policies and unemployment through a comprehensive bibliometric analysis to identify research patterns, influential contributions, and emerging trends. The investigation analyzes 867 publications from Scopus and Web of Science (WoS) databases (1966-2024) using ScientoPy for bibliometric analysis and VOSviewer for network visualization, encompassing publication patterns, citation analysis, institutional contributions, subject areas, and keyword analysis. Results reveal contrasting database dynamics, with WoS demonstrating growth (AGR: 3%, ADY: 30) despite fewer publications (379), while Scopus maintains broader coverage (488 publications) despite negative growth (AGR: -1%). Business and Economics emerges as the dominant discipline with 357 publications. The International Labour Review leads source of publications with 16 papers, while Gordon (1997) represents the most influential work with 326 citations. The study's reliance on Scopus and WoS databases creates potential Western-centric bias, particularly evident in the geographical concentration of European and Australian institutions. This analysis provides strategic insights for researchers and policymakers while highlighting opportunities for geographical diversity and interdisciplinary approaches, emphasizing the need to incorporate regional databases and emerging themes, especially in digital labor markets and post-pandemic employment patterns.